Novel polymer-modified electrodes for batch injection sensors and application to environmental analysis - Brett, Christopher M. A. (1999)
Various polymer coatings have been investigated for the protection of mercury thin-film electrodes in the square wave anodic stripping voltammetry of environmental samples using batch injection analysis, with injection of untreated samples of volume 50 [mu]l directly over the sensing electrode. Polymer coatings studied include those with controlled porosity, and cation-exchange polymers based on sulphonated polymers. Of the polymers tested, films of ca. 1 [mu]m thickness made from Nafion® mixed with 5% poly(vinyl sulphonic acid) were found to give the best results in tests with the model surfactants Triton-X-100 detergent, sodium dodecyl sulphate and protein standard. The validity of the approach is demonstrated by application to real samples.